2022
DOI: 10.3389/fmicb.2022.837182
|View full text |Cite
|
Sign up to set email alerts
|

Effects of β-Carotin and Green Tea Powder Diets on Alleviating the Symptoms of Gouty Arthritis and Improving Gut Microbiota in C57BL/6 Mice

Abstract: As a chronic metabolic disease caused by disorders of purine metabolism, gout has shown increasing incidence rate worldwide. Considering that gout is not easily treated and cured, further studies are explored to prevent gout development through diet modification. Both β-carotin and green tea powder are rich in dietary fiber, which helps maintain the balance of gut microbiota in humans. The aim of this study was to investigate the effects of β-carotin and green tea powder diet on the prevention of gouty arthrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…Studies have shown that at the genus level, 12 genera ( Bacteroides , Parabacteroides , Gemella , Lactococcus , Anaerostipes , Dorea , Anaerotruncus , Allobaculum , Holdemania , Desulfovibrio , Morganella , and Proteus ) were enriched in HUA rats induced by a high-fat diet containing 10% yeast extract, but 10 other genera ( Rothia , Collinsella , Prevotella , Odoribacter , Lactobacillus , Streptococcus , Clostridium , Dehalobacterium , Ruminococcus , and Anaeroplasma ) were less abundant ( Yu et al., 2018 ). Another study showed that the relative abundances of Muribaculaceae, Bacteroides , and Lachnospiraceae were significantly decreased in a gout model induced by MSU crystals combined with high-fat diet feeding compared with the normal control group ( Feng et al., 2022 ). In a gout model induced by a combination of MSU crystals and high-fat diet feeding, changes in the gut microbiota were induced, including increased levels of Desulfovibrio and Parabacteria ( Lin et al., 2020 ).…”
Section: The Gut Microbiota In the Pathogenesis Of Hua And Goutmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that at the genus level, 12 genera ( Bacteroides , Parabacteroides , Gemella , Lactococcus , Anaerostipes , Dorea , Anaerotruncus , Allobaculum , Holdemania , Desulfovibrio , Morganella , and Proteus ) were enriched in HUA rats induced by a high-fat diet containing 10% yeast extract, but 10 other genera ( Rothia , Collinsella , Prevotella , Odoribacter , Lactobacillus , Streptococcus , Clostridium , Dehalobacterium , Ruminococcus , and Anaeroplasma ) were less abundant ( Yu et al., 2018 ). Another study showed that the relative abundances of Muribaculaceae, Bacteroides , and Lachnospiraceae were significantly decreased in a gout model induced by MSU crystals combined with high-fat diet feeding compared with the normal control group ( Feng et al., 2022 ). In a gout model induced by a combination of MSU crystals and high-fat diet feeding, changes in the gut microbiota were induced, including increased levels of Desulfovibrio and Parabacteria ( Lin et al., 2020 ).…”
Section: The Gut Microbiota In the Pathogenesis Of Hua And Goutmentioning
confidence: 99%
“…Furthermore, inulin treatment increased the production of SCFAs (acetate, propionate, and butyrate concentrations) derived from the gut microbiota in Uox-knockout mice ( Guo et al., 2021 ), which was positively correlated with efficacy in relieving HUA. Adding dietary fiber-rich β-carotene and green tea powder to the diet reduced joint swelling and pain in mice with gouty arthritis; decreased serum UA and three proinflammatory cytokines, namely, IL-1β, IL-6, and tumor necrosis factor (TNF-α); improved the gut microbiota profile; and decreased purine and pyrimidine metabolism ( Feng et al., 2022 ).…”
Section: Gut Microbiota As a Potential Therapeutic Target In Hua And ...mentioning
confidence: 99%
“…ABCG2 is a primary transporter protein for uric acid excretion in the intestine ( 63 ). Studies have shown that tea-active ingredients can promote uric acid excretion in the intestine ( 52 ) and reduce the metabolism of purines and pyrimidines by up-regulating the expression of intestinal ABCG2 ( 64 , 65 ). In recent years, with the in-depth research related to intestinal flora, some scholars have realized that intestinal flora is expected to be a new target for treating hyperuricemia ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been shown that co-feeding of β-carotene and green tea powder in gouty mice significantly increased the positive interaction between gut microbes, which may positively in relieve gout symptoms ( Feng et al., 2022 ). Dietary administration of tuna meat oligopeptides (TMOP) alleviates hyperuricemia and renal inflammatory phenotypes.…”
Section: Treatment Of Goutmentioning
confidence: 99%